Digital Humanities as a Transdisciplinary Communication Paradigm in the Age of AI - Rusudan Makhachashvili; Ivan Semenist (Journal of Systemics, Cybernetics and Informatics)

(untitled)
Transformative shifts in the knowledge economy of the XXI century, Industry 4.0 and Web 4.0 development and elaboration of networked society, emergency digitization of all social communicative spheres due to pandemic measures have imposed pressing revisions onto interdisciplinary and cross-sectorial job market demands of university level education, curriculum design and learning outcomes. As a product of modern civilization, digital reality has become an independent format of being. Accordingly, electronic media act not only as a means of transmitting information but also reveal their own world-creating, meaning-making, and, as a consequence, communicative potential. The global digital realm stands as an integral environment, demanding new cognition and perception ways via complex philosophic, cultural, social, and linguistic approaches, providing unlimited opportunities for human intellect, communicative development, and research. The consequent functional tasks to meet this challenge in the educational sphere worldwide are estimated as 1) to adapt the existent educational scenarios to digital, remote and hybrid formats; 2) to upgrade e-competence and digital literacy of all stakeholders of the educational process and industry; 3) to activate complex interdisciplinary skillsets, otherwise latent or underutilized in the professional interaction; 4) to introduce functional technical solutions for facilitation of formal and informal educational workflow and communication. The context of the erupted military intervention in Ukraine and the ensuing information warfare in various digital ambients (social media, news coverage, digital communications), the specific value is allocated to the enhanced role of digital humanism as a tool of the internationally broadcast strife for freedom and sovereignty.